Orange-fleshed Sweetpotato on the Home Grown School Feeding Menu in Nigeria and Ghana - International Potato Center (2016)
Starting in early 2015, under two projects, orange-fleshed sweetpotato (OFSP) was included on the menu once a week at eight schools in Osun State, Nigeria. In September 2015, the number of schools was increased to 17, and in September 2016 an additional 100 were added. Local farmers are supplying over 8 tons of OFSP weekly to feed 41,216 pupils. Further, nutritionally enhanced bread made with OFSP is being offered at 10 schools. In Ghana, pilot school feeding efforts began in July of 2016 with a nutritious OFSP meal offered one day a week to students at 2 schools in Kumbungu District in the Northern Region.